Identifying a “new” social variable: sociospatial distance from the Old Order Mennonites - Neuhausen, Miriam (University of Pennsylvania working papers in linguistics, 2025)
The Mennonites in southern Ontario represent a continuum of religious groups, ranging from the traditional Old Order Mennonites, who reject modern technology and participation in mainstream society, to the most liberal Conference Mennonites, who are socially integrated in mainstream society. Not much is known about Mennonite English, which is acquired as a second language (in traditional groups) or as a first language (in liberal groups). In this study, I present a “new” (to the academic discourse) social variable which I identified during ethnographic fieldwork with the Mennonites: the sociospatial distance from the Old Orders. The variable captures the three dimensions of social mobility, dialect contact, and network density. Based on a case study on Canadian Raising, I illustrate how the variable accounts for the social and linguistic complexities of the individual speakers. The analysis reveals that the traditional Old Order Mennonites and Mennonites who were never affiliated with the Old Order group pattern similarly (and differ from previous documentations of Canadian English), while speakers who left the Old Order church for a more liberal Mennonite denomination produce significantly different vowels (and linguistically approach the mainstream). The findings suggest that these speakers’ internal and external conflicts, grounded in their close contact with both social realities, is reflected in their systematic deviation from Mennonite English. This study contributes to an emerging body of research on the linguistic negotiation of conflicting identities (Levon 2015, Jones 2018, VanderStouwe 2024).